2017
DOI: 10.1038/nmicrobiol.2016.267
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory drug mesalamine targets bacterial polyphosphate accumulation

Abstract: Mesalamine serves as the gold standard in treating ulcerative colitis. However, its precise mechanism(s) of action remains unclear. Here, we show that mesalamine treatment rapidly decreases polyphosphate levels in diverse bacteria, including members of the human gut microbiome. This decrease sensitizes bacteria towards oxidative stress, reduces colonization and attenuates persister cell and biofilm formation, suggesting that mesalamine aids in diminishing the capacity of bacteria to persist within chronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 25 publications
3
124
0
Order By: Relevance
“…Our data revealed that accumulation of polyP serves as an efficient posttranslational stress response system that protects Pseudomonas against the deleterious effects of all three major neutrophilic oxidants. We recently identified mesalamine, the gold standard in treating patients with mild to moderate ulcerative colitis, as a potent inhibitor of bacterial polyP production in a wide range of bacteria, including P. aeruginosa PA14 (Dahl et al ., ). We now wondered whether mesalamine treatment could be used to sensitize PA14 toward the three physiological oxidants, making it potentially a powerful drug to combat P. aeruginosa infections within chronically inflamed environments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our data revealed that accumulation of polyP serves as an efficient posttranslational stress response system that protects Pseudomonas against the deleterious effects of all three major neutrophilic oxidants. We recently identified mesalamine, the gold standard in treating patients with mild to moderate ulcerative colitis, as a potent inhibitor of bacterial polyP production in a wide range of bacteria, including P. aeruginosa PA14 (Dahl et al ., ). We now wondered whether mesalamine treatment could be used to sensitize PA14 toward the three physiological oxidants, making it potentially a powerful drug to combat P. aeruginosa infections within chronically inflamed environments.…”
Section: Resultsmentioning
confidence: 97%
“…Defense systems against microbicidal oxidants 343 treating patients with mild to moderate ulcerative colitis, as a potent inhibitor of bacterial polyP production in a wide range of bacteria, including P. aeruginosa PA14 (Dahl et al, 2017). We now wondered whether mesalamine treatment could be used to sensitize PA14 toward the three physiological oxidants, making it potentially a powerful drug to combat P. aeruginosa infections within chronically inflamed environments.…”
Section: Mesalamine Increases Pa14 Sensitivity Toward All Three Oxidantsmentioning
confidence: 99%
“…Intestinal pH measurements demonstrated a significant decrease in pH in the SDF‐diet‐fed animals, especially those in the HF group, but a significant shift to higher values in the RM group. The reduced intestinal pH could be beneficial for the proliferation of probiotics but inhibitory for harmful bacteria …”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that the transient accumulation of polyP in the early phase of starvation may facilitate the formation of INH‐tolerant mycobacteria. 5‐Aminosalicylic acid (5‐ASA, also known as mesalamine) is an inhibitor of PPK1 (Dahl et al ., ) and had no effect on the growth of Msm (Supporting Information Fig. S4C).…”
Section: Resultsmentioning
confidence: 93%
“…However, the accumulation of polyP was reduced (Supporting Information Fig. S4D) (Dahl et al ., ), and the percentage of INH‐tolerant cells in the logarithmic growth phase and under nutritionally starved conditions was reduced (Fig. B).…”
Section: Resultsmentioning
confidence: 97%